In Search of Invisible Cows. Collaboration, Resistance and Affection in Human-Animal Relationships on Contemporary Dairy Farms. - Taija Kaarlenkaski; Annika Lonkila (Finland, 2022)
The notion of “invisible cows” has become popular in Finnish dairy production. This concept emerges in a very specific historical context: Increasing herd size, changing technological infrastructure in cowsheds, and the transformation of farmer identities all contribute to a need for more intensified forms of collaborative practices between humans and animals. An invisible cow is healthy, corporally compliant, obedient, easy and collaborative both in its body and behaviour. Invisible cows form a uniform herd in which individual animals require minimal care from farmers. In this paper, we explore how this new ideal is manifested on dairy farms, and how it changes the agencies of both farmers and animals and affects human-animal relationships. We examine the notions of collaboration, resistance and human-animal affection and aim to build links between these concepts. Our discussion of everyday work on dairy farms reveals the unattainability of invisibility. In various ways cattle resist their enactment as see-through members of the herd. Furthermore, invisibility can also be resisted by farmers who embrace their relations with specific animals who fail to stay invisible. Our paper contributes to a more complex understanding of the intertwinement of human and animal agency
within dairy husbandry and argues that collaborative and resistant practices are always entangled.